Re-thinking aesthetics: Rogue essays on aesthetics and the art - Berleant, Arnold (USA Ashgate, 2004)
The essays, collected by Berleant in this volume all express the impulse to reject the received wisdom of modern aesthetics: that art demands a mode of experience sharply different from others and unique to the aesthetic situation, and that the identity of the aesthetic lies in keeping it distinct from other kinds of human experience, such as the moral, the practical, and the social. Berleant shows, on the contrary, that the value, the insight, the force of art and the aesthetic are all enhanced and enlarged by recognizing their social and human role, and that this recognition contributes both to the significance of art and to its humanizing influence on what we like to call civilization.